63.6k views
4 votes
How would you explain to someone the rules of a horizontal translation where we are subtracting from the inputs(within the parenthesis) before evaluating the function

How would you explain to someone the rules of a horizontal translation where we are-example-1

1 Answer

5 votes

Answer:

Ok, we know that we can write a horizontal translation as:

y' = f(x - A)

where if A is positive, this moves the graph of f(x) A units to the right.

Why is this?

Ok, let's compare:

y = f(x)

and

y' = f(x - A)

in y, when x = 0 we have f(0).

While to have this same point in y', we need to evaluate in x = A.

f(A - A) = f(0).

Then the value f(0) is now at x = A, this means that the point moved A units to the right.

And you can do this for all the values, so you will find that the entire graph of f(x) has ben moved A units to the right.

User Zakiyah
by
4.5k points